Developing the Integrated Control Systems Media for Enhancing the Electrification Competency of Electric Railway Drive - Rizqi Ervani (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2025)
This study aimed to determine the operation of the integrated control media for the traction system in electric railway drives at the Polytechnic, to assess the feasibility of the integrated control media for the traction system, and to produce an effective integrated control media for the traction system that can be used to increase the electrification competence of electric railway drives. This study was conducted using a development research approach, employing the RAD (Rapid Application Development) and ASSURE methods. The subjects of this study were 39 students from the Madiun State Polytechnic Railway. Data was collected using observation sheets, interview sheets, media questionnaires, module questionnaires, and tests. Validation of the questionnaire instrument was carried out using Aiken's-V formula and Pearson Product-Moment correlation, while the reliability test of the test instrument used Cronbach's Alpha. The validity coefficient of the material and media questionnaire instrument falls into the category of